Prácticas y uso de recursos forestales por las comunidades indígenas Chapras en la cuenca media alta de la quebrada Pushaga. Loreto 2024 - Ramos Davila, Julio Cesar (2024)
It is a non-experimental study of the exploratory, descriptive, cross-sectional type, with the purpose of evaluating the practices and use of natural resources and socioeconomic perceptions in four Chapras indigenous communities of the Pushaga ravine in Loreto. The sample is communities from Puerto Pijuayal, Chingana, Panguanita and Naranjal and the leaders of the Chapra and Apus Autonomous Government. Cronbach's alpha reliability reports a value of 0.799. Descriptive statistics were used to present the data in graphs and tables. The majority of the economically active population faces few employment opportunities, limited to forestry extraction and subsistence agriculture. The lack of employment options and dependence on external sources, such as temporary work in the oil sector, creates economic instability in households. Therefore, the levels of poverty, the high rate of illiteracy and the scarcity of water, sanitation, and electricity services show a low quality of life in the communities. But it is evident that the presence of social programs is positive, but insufficient to address the needs of comprehensive development. The prevalence of preventable diseases and the lack of health infrastructure and personnel reflect the deficiencies in access to health care. Reliance on traditional practices is a resilience strategy, but it is limited in the face of certain health problems that require specialized medical care. The adaptability of communities and the use of sustainable agricultural practices show ecological knowledge and a balanced relationship with the environment. Traditional techniques, such as soil management and taking advantage of natural fertility, help sustain subsistence agriculture that respects natural cycles. Communities rely heavily on local flora and fauna and have developed skills that contribute to the sustainability and preservation of natural resources. However, this dependence also makes them vulnerable to external factors, such as the environmental impacts of oil activity in nearby areas.